Effective Marketing Strategy: Analysis of Advertising Appeals and Nct Dream Brand Ambassadors Through Brand Image Mediation on Somethinc Product Purchase Intention - Sunandika, Tarisya Adzani; Widodo, Arry (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The aim of this research is to determine the influence of advertising appeals and brand ambassadors on purchase intention with brand image as an intervening variable in certain consumers aged 17-25 years in Bandung City. The research method used in this research is a quantitative method, with Structural Equation Model (SEM) analysis techniques using SMART PLS software. The sampling technique in this research used a purposive sampling technique, the number of samples obtained was 384 respondents. The results of the research show that the advertising appeals variable on brand image has no significant effect, while the brand ambassador variable on brand image has a significant effect, the advertising appeals, brand ambassador and Brand Image variables have positive and significant results on Purchase Intention . However, the results of advertising appeals testing on purchase intention through brand image did not have a significant effect. Meanwhile, brand ambassadors have a significant influence on purchase intention through brand image. The conclusion in this research is that the advertising appeals, brand ambassadors, brand image of some products are very good, consumers believe that some products are a reliable company.